Planktic foraminiferal productivity and test-size at Pacific ODP Site 198-1209 and ODP Site 198-1210, Shatsky Rise, during the the Early Eocene Climatic Optimum (EECO, ~53-49 Ma) - Giulia Filippi; Ruby Barrett; Daniela N Schmidt; Roberta D extquotesingleOnofrio; Thomas Westerhold; Valentina Brombin; Valeria Luciani (PANGAEA, 2024)
We record changes in planktic foraminiferal assemblage abundance, test size and carbonate production during the Early Eocene Climatic Optimum (EECO; 53-49 Ma) at the Pacific Ocean Shatsky Rise ODP Sites 198-1209/1210. We measured stable Carbon and Oxygen bulk isotope (VPDB extperthousand) and weight percent coarse fraction (CF; %) for site 1210, while for site 1209 stable isotope data and CF are from Westerhold et al., (2018). We also determined the Fragmentation index (%), Foraminiferal Mass Accumulation Rate (FMAR; g/cm^2/ka), planktic foraminiferal assemblage abundances and test size 95 percentile (μm) at sites 1209 and 1210 . Depht in revised meter composite depth, and Age Model (Ma) at sites 1209 and 1210 are according to Westerhold et al. (2018), the labels of the Carbon Isotope Excursions (CIEs) recorded during this interval refers to Westerhold et al. (2017).